Kinerja Keuangan Terhadap Probabilitas Tindak Fraudulent Financial Statement - Rosya, Dianda Talitha; Aminah, Aminah; Riswan, Riswan (Universitas Muhammadiyah Metro, 2024)
Fraudulent Financial Statement (FFS) is an act of manipulating financial statements with the aim of making a company's financial condition look better than the actual condition. This study aims to empirically examine the effect of financial performance in detecting Fraudulent Financial Statements controlled by Company Size. Financial performance is measured using Financial leverage, Profitability, and Liquidity. Fraudulent Financial Statements are measured using the Beneish M-Score model. This research method uses purposive sampling as the sample determination. The research sample was 60 samples covering 20 state-owned companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. The data processing technique uses logistic regression analysis with SPSS as the analysis tool. The results of this study provide empirical evidence that there is a significant effect of Financial leverage, Profitability, and Liquidity on fraudulent financial statements. This proves that financial performance allows it to be used as a predictor in detecting fraudulent financial statements. Keywords: Fraudulent Financial Statement; Financial leverage; Profitability; Liquidity; Company Size.